2021
DOI: 10.1186/s12933-021-01264-z
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin effect on endothelial dysfunction in diabetic patients with atherosclerotic disease: a randomized active-controlled trial

Abstract: Background The glucose-lowering independent effect of sodium glucose cotransporter-2 inhibitors (SGLT2i) on arterial wall function has not yet been clarified. This study aims to assess whether SGLT2i treatment can attenuate endothelial dysfunction related to type 2 diabetes mellitus (T2D) compared with glucose-lowering equivalent therapy. Methods In a prospective, open-label, single-center, randomized clinical trial, 98 patients with T2DM and carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 44 publications
0
41
0
2
Order By: Relevance
“…Instead, the change in FMD after I/R was not different between the two regimens. In an intragroup exploratory analysis, the study demonstrated that dapagliflozin improved FMD in individuals with severe arterial wall dysfunction when compared to glibenclamide, as well as when compared with baseline values [126]. The positive results on FMD obtained in this study likely depend on the recruitment of patients with more severe arterial wall dysfunction than prior trials and on a carefully balanced reduction in blood glucose in the two study arms.…”
Section: Results From Clinical Studiesmentioning
confidence: 54%
See 1 more Smart Citation
“…Instead, the change in FMD after I/R was not different between the two regimens. In an intragroup exploratory analysis, the study demonstrated that dapagliflozin improved FMD in individuals with severe arterial wall dysfunction when compared to glibenclamide, as well as when compared with baseline values [126]. The positive results on FMD obtained in this study likely depend on the recruitment of patients with more severe arterial wall dysfunction than prior trials and on a carefully balanced reduction in blood glucose in the two study arms.…”
Section: Results From Clinical Studiesmentioning
confidence: 54%
“…The recently published ADDENDA-BHS2 aimed to evaluate whether dapagliflozin, regardless of its glucose-lowering effect, could mitigate the ED and increase the endothelial resilience to I/R injury in T2DM patients with atherosclerotic disease [126]. The study demonstrated that a 12-week course of treatment improved vasomotor function in both macro-and microcirculation as compared to glibenclamide, in a setting of comparable glucose lowering between the two groups.…”
Section: Results From Clinical Studiesmentioning
confidence: 99%
“…More recently, in a study of 97 patients with DM2, Sposito et al showed that treatment with dapagliflozin improved endothelial function relative to glibenclamide as determined by Doppler-recorded reactive vasodilation. 44 These findings indicate that the effect of SGLT1 inhibitors on sympathetic tone and vascular remodeling can contribute to their benefits for patients with HF.…”
Section: Reduced Sympathetic Stimulusmentioning
confidence: 85%
“…Dapagliflozin also augments peripheral microvascular endothelial function in patients with poorly controlled T2DM that corresponds to reductions in patient's blood pressure and abdominal fat mass [57]. Furthermore, an active-controlled trial found that dapagliflozin corrects endothelial dysfunction in T2DM patients with atherosclerotic disease [58]. In contrast, a prospective, randomized, blinded end point study showed that dapagliflozin preserves renal artery vasodilating capacity in T2DM patients with hypertension, but it fails to modify FMD [59].…”
Section: Effect Of Sglt2 Inhibitors On Endothelium-dependent Vasodilationmentioning
confidence: 99%